The Strategic Use of Information and Communication Technology on The Gaps Model of Service Quality in Banking Industry - Tan, L.H.; Chew, B. C.; Hamid, S. R. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
The impact of ICT on customer service has risen considerably in recent years. This can be seen by the number of papers published and in particular by financial- and banking-related journal. To establish the field further, the purpose of this paper is has twofold. First, it offers a literature review on 186 papers published from 2009 to 2015 into account and qualitative case study was based on primary data collected on 32 bank managers from 3 banks. Second, it offers a conceptual framework to summarize the research in this field comprising four parts. The authors illustrate the classification of ICT impact on Customer Service in four parts: Listening Gap, Service Design and Standard Gap, Service Performance Gap and Service Communication Gap.